Differentiated Learning to Solve Arabic Learning Problems Faced by Non-muslim Learners - Nurlatifah; Sugih Ardianto; Ammar Ahmed; Uus Ruswandi; Mohamad Eri Hadiana (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
This study examines the application of differentiated learning to address challenges faced by non-Muslim students learning Arabic in the 11th-grade Science class at SMAN 11 Bandung. Differentiated learning, which adjusts teaching methods to students' readiness, interests, and learning profiles, was implemented to tackle linguistic and non-linguistic barriers in Arabic language acquisition. A qualitative case study method was employed, involving interviews, observations, and document analysis to collect data. Key findings indicate that non-Muslim students face difficulties in phonetics, vocabulary, and grammar, compounded by non-linguistic issues such as limited teaching materials and environmental distractions. Differentiated learning strategies—tailored content, processes, and products—helped mitigate these challenges by aligning teaching with individual needs. The study highlights the universal appeal of Arabic as a language and recommends employing differentiated learning to enhance inclusivity and learning outcomes in diverse classrooms. This approach provides a framework for educators to foster equitable learning opportunities, ensuring all students can thrive academically